2000
DOI: 10.1161/01.cir.102.suppl_3.iii-35
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid Aortic Valves Are Associated With Aortic Dilatation Out of Proportion to Coexistent Valvular Lesions

Abstract: Background-Bicuspid aortic valves (BAVs) are associated with premature valve stenosis, regurgitation, and ascending aortic aneurysms. We compared aortic size in BAV patients with aortic size in control patients with matched valvular lesions (aortic regurgitation, aortic stenosis, or mixed lesions) to determine whether intrinsic aortic abnormalities in BAVs account for aortic dilatation beyond that caused by valvular hemodynamic derangement alone. Methods and Results-Diameters of the left ventricular outflow tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
183
2
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(218 citation statements)
references
References 24 publications
23
183
2
10
Order By: Relevance
“…They observed comparable degrees of aortic regurgitation, stenosis or mixed lesions, and concluded that intrinsic pathology appears to be responsible for aortic enlargement. 21 These observations support the hypothesis that BAV and TAA are independent manifestations of a single gene defect in a subset of BAV families. 21,32,61 The risk of dilatation of the thoracic aorta might therefore be increased in some first-degree relatives of BAV patients, even in the absence of a bicuspid aortic valve.…”
Section: Bicuspid Aortic Valve: Clinical and Genetic Aspectssupporting
confidence: 76%
See 3 more Smart Citations
“…They observed comparable degrees of aortic regurgitation, stenosis or mixed lesions, and concluded that intrinsic pathology appears to be responsible for aortic enlargement. 21 These observations support the hypothesis that BAV and TAA are independent manifestations of a single gene defect in a subset of BAV families. 21,32,61 The risk of dilatation of the thoracic aorta might therefore be increased in some first-degree relatives of BAV patients, even in the absence of a bicuspid aortic valve.…”
Section: Bicuspid Aortic Valve: Clinical and Genetic Aspectssupporting
confidence: 76%
“…21 These observations support the hypothesis that BAV and TAA are independent manifestations of a single gene defect in a subset of BAV families. 21,32,61 The risk of dilatation of the thoracic aorta might therefore be increased in some first-degree relatives of BAV patients, even in the absence of a bicuspid aortic valve. Vice versa, a limited number of studies suggest that BAV might be more prevalent in familial thoracic aneurysms and dissections (FTAAD) and in some hereditary connective tissue disorders associated with an increased risk of aortic aneurysms (for example Marfan syndrome).…”
Section: Bicuspid Aortic Valve: Clinical and Genetic Aspectssupporting
confidence: 76%
See 2 more Smart Citations
“…A comparison between the outcome of Costello syndrome with MAT in young children and Noonan syndrome with multiple lentigines with older patients with conduction defects or ventricular arrhythmia associated with HCM is not meaningful (Table IV), but they represent the RASopathies currently with the most frequent and distinctive ''arrhythmia phenotypes.'' Mild aortic dilation in Costello syndrome was not related to bicuspid aortic valve [Keane et al, 2000] and may be a manifestation of an intrinsic vasculopathy. Prospective surveillance in the other RASopathies is needed to determine if aortic dilation, coronary artery dysplasia and hypertension (systemic and pulmonary) constitute a vasculopathy.…”
Section: Comparison To Other Rasopathiesmentioning
confidence: 79%